Transformations of the Heritage Landscape Induced by Urban and Tourist Public Policies in Public Spaces in the City of São Luís (Maranhão) - Santos, Saulo Ribeiro dos; Ferreira, Deborah Emilly Soares; Marques, Matheus Andrade (Anais Brasileiros de Estudos Turísticos, 2022)
This paper is dedicated to collaborate with a discussion pertinent to the investigative interests of geography science, because it brings to light an analysis of the transformation processes that the urban space goes through. In this sense, the city of São Luís (Maranhão, Brazil) was used as an analytical spatial cutout of the referred phenomenon, in a specific way, through the João Lisboa Square and the Largo do Carmo, environments located in the historical center of the capital of Maranhão that is recognized as world heritage city by UNESCO. Thus, these are places of utmost relevance to the local society, since they preserve a patrimonial landscape, dating from the colonial period of the city. Thus, we have as research objective: to analyze the landscape changes of these areas from tourism-related interventions. To succeed, we carried out bibliographic research, analysis of public policies, and field activities. As a result, it was found that although the places preserve their landscape configurations, due to their listing, their dynamics of use and occupation were modified by the insertion of tourism in the places.